INTRODUKSI TEKNOLOGI PENGOLAHAN HIJAUAN PAKAN DAN LIMBAH SAPI SEBAGAI SUATU SISTEM USAHA PERTANIAN TERPADU DI TEPIAN DAERAH ALIRAN SUNGAI (DAS) PROGO KECAMATAN LENDAH KULONPROGO - Utomo, Setyo; Rasminati, Nur (Universitas Negeri Yogyakarta, 2010)
The aim of IPTEKS activity application is to increase the development community by raising of productivity of beef cattle. The activity of raising beef cattle productivity was done by preservation of forage as silage and straw fermentation, waste of beef cattle as biogas, and organic fertilizer. It was done in 4 villages of Lendah subdistrict, Kulon Progo regency and had cooperation with BPP Lendah. The methods used were education and training by direct application of using technology. This training was followed by 19 groups of cattle in 4 villages those are Jatirejo, Sidorejo, Gulurejo and Ngentakrejo. The material consist of 3 topics those are preservation of forage as silage and straw fermentation, waste of beef cattle as biogas and organic fertilizer technology. Each village made the silo, silage, and bokashi fertilizer. Making of biogas instalation was centered in Nglatiyan I, Ngentakrejo village. The result showed that the societies of 4 villages have made the silo, preserving of forage as silage and straw fermentation for feed, processed waste of beef cattle as organic fertilizer for their own fields consciously. Biogas instalation with double system that has been built can be used 4 – 5 hours/day optimally for doing household activity, espsecially for cooking. It can be concluded that 4 villages have built the silos, doing preservation of forages in form of silage and straw fermentation, processing waste of cattle as bokashi fertilizer. Biogas production can be used by societies in Nglatiyan I optimally.